ANALISIS RISIKO PADA PROYEK KONSTRUKSI PERUMAHAN DENGAN METODE HOUSE OF RISK (HOR) : Studi Kasus Proyek Kontruksi Perumahan PT ABC - Siti Aisyah Maharani (2021)
Construction project activities have a risk to their implementation. The risks in construction projects however cannot be eliminated but it can be minimized or transferred from one party to another. Thus, the risk management of construction projects has an important role in achieving the development goals of a project. This research is a case study on one of housing construction projects, PT. ABC. The purpose of this study is to analyze the risks on the project and to find out how corrective handling and mitigation minimize the risk to residential construction projects by the House of Risk method. From the results of the risk analysis of the HOR method visualized with the Pareto diagram, there are 7 priority risk agent items with 8 proposed mitigation actions prioritized to be realized as a response to the handling and mitigation of risks in residential construction projects at PT ABC.